Research of the Methylation Status of miR-124a Gene Promoter among Rheumatoid Arthritis Patients - Qiao Zhou; Li Long; Guixiu Shi; Jing Zhang; Tong Wu; Bin Zhou (Clinical and Developmental Immunology)
Objective. To analyze the methylation status of miR-124a loci in synovial tissues of rheumatoid arthritis (RA) patients using methylation-specific polymerase chain reaction (MSP). Materials and Methods. DNA obtained from the frozen tissue of 7 RA samples, 6 osteoarthritis (OA) samples, and 3 healthy controls were undergoing bisulfite conversion and then analyzed for miR-124a promoter methylation using MSP assay. Results. miR-124-a1 and miR-124-a2 promoter methylation were both seen in 71.4% of RA samples compared to 16.7% of OA samples. miR-124-a3 promoter methylation was seen in 57.1% of RA samples and 0% of OA samples. All the three loci were unmethylated in 3 healthy controls. Conclusion. The methylation status of miR-124a seen in this study concurs with that reported in tumor cells, indicating epigenetic dysregulation constituents, a mechanism in the development of rheumatoid arthritis.